Marketing Communication Strategy for Private School Promotion and Development Through Students' Parent Support: A Case Study at SD Gracia, Surabaya - Iswandono, Joko; Utami Ady, Sri; Sayidah, Nur (International Journal of Education and Digital Learning (IJEDL), 2025)
Elementary school education is a compulsory education and an important stage in the learning process, so choosing a wise elementary school is crucial. The large number of elementary schools in Indonesia, both public and private, has created fierce competition between educational institutions. Especially after the implementation of zoning regulations, private elementary schools have also been affected and some have been forced to stop operating due to a lack of students. In addition to improving the quality of education, schools are required to have an effective promotional strategy to attract the interest of the community as potential customers. One of the promotional strategies that can be applied is the promotional mix strategy. SD Gracia Surabaya, as one of the private elementary schools, also applies a promotional mix in its strategy. Therefore, this study focuses on discussing in depth how the promotional strategy implemented by SD Gracia Surabaya attracts the support of parents. This study uses a descriptive qualitative approach with a purposive sampling technique to determine the research sample. The data obtained consists of primary and secondary data collected through interviews, observations, and documentation. To ensure data validity, the researcher uses source triangulation and technical triangulation techniques. After the data is validated, data reduction, data presentation, and verification of conclusions are carried out in the analysis. The results of the study show that SD Gracia Surabaya implements a promotional mix strategy involving advertising, personal selling, and public relations activities.